Concentrations and dimensions of coated and uncoated asbestos fibres in the human lung. Issue 1 (February 1980) - Morgan, A; Holmes, A
Abstract : Concentrations and length distributions of uncoated and coated amphibole-type fibres in samples of human lung taken at necropsy were measured by optical microscopy using the membrane filter technique that enables fibres with diameters down to about 0.2 micron to be detected. The subjects included 10 who died with mesothelial tumours, three with lung cancer, and eight of other causes. Measurements of fibre concentrations are compared with those of other workers. It can be deduced from the length distributions that fibres less than 5 microns long are cleared from the lung more efficiently than longer ones. The clearance of short fibres appears to be inhibited in subjects with asbestosis, however. The length distributions of uncoated and coated fibres were dissimilar. In general, few fibres less than 10 microns in length were coated and few greater than 40 microns in length were uncoated. The probability of a fibre of given length, however, becoming coated varied considerably from subject to subject. Possible reasons for this are discussed.